Message Reminders Encouraging Brisk Walking by Considering the Dynamic Factor of Cognitive Fatigue - Symons, Michelle; Vandebosch, Heidi; Cutello, Clara Alida; Poels, Karolien (European journal of health communication, 2022)
Physical inactivity and sedentary behaviours are leading risk factors for preventable health problems worldwide. Therefore, several smartphone-based interventions have tried to enhance physical activity (PA) through goal reminders based on relatively stable characteristics. However, time-varying factors, such as cognitive fatigue, may act as barriers to engagement in PA. This study aims to unravel what type of goal reminder messages are effective for enhancing PA in situations of cognitive fatigue. First, using a 3 x 3 between-subjects design, we evaluated the effectiveness of goal reminders matched with real-time goals under different levels of cognitive fatigue. This study did not find evidence that the tested goal reminders, intended to be adapted to the real-time goals of the participants, were more effective in promoting PA than goal reminders not adapted to individuals’ real-time goals. Second, to better understand how to design future reminders, two questions explored what format and what content participants considered to be helpful when feeling cognitively fatigued. Results show that GIFs, textual reminders, and pictures are suitable formats in smartphone-based interventions and that humorous content is preferred when feeling cognitively fatigued. These findings contribute to the development of just-in-time adaptive interventions that consider dynamic factors to promote PA.